Molecular Modeling, Synthesis, and preliminary pharmacological evaluation of New Sulfonamide Derivatives as Selective Carbonic Anhydrase XII and IX inhibitors (Research) - Samer Tareq Jasim; Monther F. Mahdi (College of Pharmacy / Mustansiriyah University, 2024)
New benzene sulfonamide compounds 4-10 was modeled at the molecular level to reveal binding opportunities, bond length, angle, and energy scores in the CA II, CAXII, and CAIX active sites. To test their cytotoxic effect against the AMJ-13 Iraqi breast cancer cell line, researchers synthesized the promising compounds from 4-(2-mercapto-4-oxoquinazolin-3(4H)-yl) benzene sulfonamide 3. Derivatives 4-10 have IC50 values between 0.10 and 6.47 M, indicating potent action against the AMJ-13 cell line. The most effective of these compounds were numbers 4, 7, and 10. The highest binding scores in the active site of CAXII and CAIX were seen for the most active drugs, which may explain their inhibitory profile.